Complejidad sintáctica y construcción de narración. Análisis de una tarea de recontado en niños de preescolar - Crespo Allende, Nina; Koza, Walter; Sotelo, Eva (Círculo de Lingüística Aplicada a la Comunicación, 2017)
Syntactic complexity and narrative construction. Analysis of a retelling task by preschool children. The goal of this paper is to establish how children give complexity to their syntax in the different moments of a narration, according to a discursive functionalist approach. For this purpose, 30 preschool children were selected and they participated of a retelling activity. The children’s oral productions were analyzed on the basis of story grammars, clause packaging and it clauses: isotaxis, parataxis and hypotaxis. The results show that children construct more clause packaging and with more complexity in the causal schema of story (first event and character action) and in the manifestation of inner world characters. The evidence supports the idea of notion of a strategic use of the syntax and of the textual modality incidence in it.